32. ASSESSMENT OF THE READINESS FOR HOSPITAL DISCHARGE AFTER SURGERY FOR DISC AND LUMBAR SPINAL DISC AT THE DEPARTMENT OF SPINE SURGERY OF VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Target: Assessing the readiness to discharge patients undergoing spinal surgery at the spinal surgery department of Viet Duc University Hospital.Methods: A cross-sectional descriptive study was conducted on 120 patients discharged from the spine surgery department of Viet Duc University Hospital from February 2024 to June 2024; Use the Readiness for Discharge Scale (RHDS) to survey information about patients' readiness for discharge from the hospital.Results: According to statistical results, the male/female ratio is 1,6/1; Average age: 48,9 ± 12,8 years. The total average score of the RHDS is 182,35 ± 12,23, in which: the personal status score is 8,08 ± 0,51; knowledge score is 8,54 ± 0,92; The coping ability score is 8,92 ± 0,78 and the social support score was 9,69 ± 0,66.Conclusion: The readiness for discharge of 120 spine surgery patients was high.Recommendations: Identifying factors that predict readiness or lack of readiness is necessary to determine the appropriate timing of discharge and post-discharge follow-up needs. Therefore, more research needs to be conducted to assess patients' readiness for discharge, then improving the quality of care and patient satisfaction.
Keywords: Readiness for hospital discharge; spine surgery; hernitated disc; patients